The biological potential of a product containing Pythium oligandrum against Uncinaria stenocephala (Railliet, 1884) larvae - Luca, Iasmina; Imre, Mirela; Ilie, Marius Stelian; Oprescu, Ion; Dărăbuş, Gheorghe (Journal of the Hellenic Veterinary Medical Society, 2022)
Pythium oligandrum is an oomycete commonly used in the biological control of plant and vegetable pests. In veterinary medicine is used to treat dermatophytosis produced by Microsporum canis. It acts as an antagonist, negatively influencing the development of other fungi. Through hydrolytic enzymes, such as kinase and cellulase, it destroys the cell wall and the internal cytoplasmic content. Many fungi are considered nematophagous. This potential has not been exploited for Pythium oligandrum, which is why in this study the potential larvicidal action against Uncinaria stenocephala larvae was investigated. Ecosin® product, which contains P. oligandrum and other excipients, was used. A solution was prepared according to manufacturer. The Uncinaria stenocephala larvae were exposed to this substance and the action was investigated after 7 days. The results obtained showed 37.23% larval reduction. Being an eco-friendly product, further studies are needed to improve the protocol for its use in cleaning spaces and surfaces in veterinary clinics, where various parasitic forms (larvae or eggs) are found.